Effects of up to 15 years of recombinant human GH (rhGH) replacement on bone metabolism in adults with Growth Hormone Deficiency (GHD): The Leiden Cohort Study. (5th June 2014) - Appelman‐Dijkstra, Natasha M.; Claessen, Kim M. J. A.; Hamdy, Neveen A. T.; Pereira, Alberto M.; Biermasz, Nienke R.
Summary Background Growth hormone deficiency (GHD) in adulthood may be associated with a decreased bone mineral density (BMD), a decreased bone mineral content (BMC) and an increased fracture risk. Recombinant human GH (rhGH) replacement induces a progressive increase in BMD for up to 5–7 years of treatment. Data on longer follow‐up are, however, scarce. Methods Two hundred and thirty‐adult GHD patients (mean age 47·1 years, 52·6% female), of whom 88% patients had adult‐onset (AO) GHD, receiving rhGH replacement for ≥5 years were included in the study. Most patients had multiple pituitary hormone deficiencies. Bone turnover markers, BMC and BMD and T‐scores at the lumbar spine and femoral neck were evaluated at baseline, and after 5, 10 and 15 years of rhGH replacement. In addition, clinical fracture incidence was assessed. Results Mean lumbar spine BMD, lumbar spine BMC and T‐scores gradually increased during the first 10 years of rhGH replacement and remained stable thereafter. Largest effects of rhGH supplementation were found in men. In the small subset of patients using bisphosphonates, use of bisphosphonates did not impact additional beneficial effects in the long term. Low baseline BMD positively affected the change in BMD and BMC over time, but there was a negative effect of high GH dose at 1 year on the change in BMD and BMC over time. Clinical fracture incidence during long‐term rhGH replacement was 20.1/1000 py. Conclusions Fifteen years of rhGH replacement in GHD adults resulted in a sustained increase in BMD values at the lumbar spine, particularly in men, and stabilization of BMD values at the femoral neck. Clinical fracture incidence was suggested not to be increased during long‐term rhGH replacement.